Implementation of Criminal Sanctions Against the Perpetrators Criminal Acts of Personal Data Sales to Online Loan Apps - Chusnul Karimah; Ifahda Pratama Hapsari; Hardian Iskandar (LEGAL BRIEF, 2022)
Two years ago, Pandemic made conditions in the world stop because of some of the requirements in the house. Most activities are done online. This resulted in several less capable societies, especially in financial matters, which were shocking. Although the pandemic is over, its effects are still being felt due to the number of layoffs, a lack of ability in the digital world, and a number of families shrinking in size. The  conomy of the community, which has not been thriving, makes the community look for solutions to survive. In Indonesia, it appears there are many illegal pin platforms. People continued to use pinuk for their financial problems despite being unaware of the importance of personal data to someone. Knowing personal information can lead to criminal behavior. New laws on personal data protection have now been published, and there are many other written rules. The authors in this article discuss the debtor data sold by creditors to others for personal benefit. Spam ads, fake gifts, hustlers, even threats—they're all impacts of self-data sales. Aim to know the shape. The rules are written in Indonesian. Personal data of salespeople over lenders can be viewed in Article 32 Parts (1) and (2). Threats to compliance can be criminalized Article 48 In Article 32, paragraphs 1 and 2,